Reconciling predicted and measured viscosity parameters in high concentration therapeutic antibody solutions - Georgina Bethany Armstrong; Aisling Roche; William Lewis; Zahra Rattray (mAbs)
Monoclonal antibody (mAb) solution viscosity in ultra-high concentration formulations is a key developability consideration in mAb development risk mitigation strategies that has implications for downstream processing and patient safety. Predicting viscosity at therapeutically relevant concentrations remains critical, despite the need for large mAb quantities for viscosity measurement being prohibitive. Using a panel of IgG1s, we examined the suitability of viscosity prediction and fitting models at different mAb test concentration regimes. Our findings caution against extrapolation from low concentration measurements, as they lack predictive ability for ultra-high concentration regimes. For the first time, we demonstrate the importance of analyte concentration range selection, and the need for bespoke viscosity model development.